Unoccupied topological states on bismuth chalcogenides - Niesner, Daniel; Fauster, Thomas; Eremeev, S. V.; Menshchikova, T. V.; Koroteev, Yu. M.; Protogenov, A. P.; Chulkov, E. V.; Tereshchenko, O. E.; Kokh, K. A.; Alekperov, O.; Nadjafov, A.; Mamedov, N. (Physical Review B, 2012)
The unoccupied part of the band structure of topological insulators Bi2TexSe3-x (x = 0,2,3) is studied by angle-resolved two-photon photoemission and density functional theory. For all surfaces linearly dispersing surface states are found at the center of the surface Brillouin zone at energies about 1.3 eV above the Fermi level. Theoretical analysis shows that this feature appears in a spin-orbit-interaction-induced and inverted local energy gap. This inversion is insensitive to variation of electronic and structural parameters in Bi2Se3 and Bi2Te2Se. In Bi2Te3 small structural variations can change the character of the local energy gap, depending on whether or not an unoccupied Dirac state exists. Circular dichroism measurements confirm the expected spin texture. From these findings we assign the observed state to an unoccupied topological surface state.